PKM Guru-Guru Bimbel Yayasan FORSIPMA Mawar - Parulian, Dudi; Julaeha, Siti; Mufti , Abdul (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2021)
This community service aims to implement information technology-based learning using the online Mentimeter application which uses the internet network as an alternative choice for teaching and learning activities due to the Covid 19 pandemic, where the spread of the plague causes the highest number of deaths and requires social and physical distancing to break the chain. the spread of Covid 19. The Mentimeter Application Increases the knowledge of teachers in the use of online material delivery in the use of the Mentimeter application of learning. Improve teacher professionalism in using the Mentimeter application in classroom learning.In this case the writer uses the Mentimeter Application as a medium for making material or questions with Mathematics which aims to understand how to make a percentage to students, so that learning is faster or up to date as needed. So that the truth of the content of the material conveyed greatly affects the quality of the resulting value.